Petrology and volatile content of magmas erupted from Tolbachik Volcano, Kamchatka, 2012–13 - Plechov Pavel; Blundy Jon; Nekrylov Nikolay; Melekhova Elena; Shcherbakov Vasily; Tikhonova Margarita S. (My University, 2015)
Abstract We report petrography, and bulk rock, mineral and glass analyses of eruptive products of the 2012–13 eruption of Tolbachik volcano, Central Kamchatka Depression, Russia. Magmas are shoshonitic in composition, with phenocrysts of olivine and plagioclase; clinopyroxene phenocrysts are scarce. Samples collected as bombs from the active vent, from liquid lava at the active lava front, and as naturally solidified “toothpaste” lava allow us to quantify changes in porosity and crystallinity that took place during 5.25 km of lava flow and during solidification. Olivine-hosted melt inclusions from rapidly-cooled, mm-size tephra have near-constant {H2O} contents (1.19 ± 0.1 wt) over a wide range of {CO2} contents (< 900 ppm), consistent with degassing. The groundmass glasses from tephras lie at the shallow end of this degassing trend with 0.3 wt {H2O} and 50 ppm CO2. The presence of small saturation, rather than shrinkage, bubbles testifies to volatile saturation at the time of entrapment. Calculated saturation pressures are 0.3 to 1.7 kbar, in agreement with the depths of earthquake swarms during November 2012 (0.6 to 7.5 km below the volcano). Melt inclusions from slowly-cooled and hot-collected lavas have {H2O} contents that are lower by an order of magnitude than tephras, despite comparable {CO2} contents. We ascribe this to diffusive {H2O} loss through olivine host crystals during cooling. The absence of shrinkage bubbles in the inclusions accounts for the lack of reduction in dissolved {CO2} (and S and Cl). Melt inclusions from tephras experienced < 3 wt post-entrapment crystallisation. Melt inclusion entrapment temperatures are around 1080 °C. Compared to magmas erupted elsewhere in the Kluchevskoy Group, the 2012–13 Tolbachik magmas appear to derive from an unusually H2O-poor and K2O-rich basaltic parent.
Keywords: 38.37.25 Вулканология; Плоский Толбачик; Tolbachik; Kamchatka